Envelopes of adaptation - an architecture of social thresholds and flexibility: investigating the socio-technical relationship between the built edge and social surface - Moodley, Byron (School of Architecture, Planning and Geomatics, 2018)
The concept of adaptability in architecture is one that very often bears technical rather than social connotations. What are the mechanisms and systems that allow buildings to adapt to fluctuating environmental and climatic conditions? These responses are often the driving force behind design considerations, placing emphasis on the manner in which the technical resolutions facilitate appropriate adaptability and environmental response. This adaptability is generally addressed through the building envelope, which acts as the mediator between the interior conditions of a building, and the exterior conditions of its environment (Lovell, 2010). However, beyond addressing these environmental conditions, there are greater urban and social conditions that bear equal weight within any design inquiry. Building adjacencies, ethnographics, social development and imageability of spatial ordering are all fundamental factors that need to be addressed within building envelope design (Lovell, 2010). The design dissertation inquiry explores the multi-faceted nature of building envelopes as well as an architecture of internal and external thresholds. The inquiry examines ways in which building envelopes respond to both the environmental and social complexities of a context, as well as how internal and external threshold and edge conditions can be design generative and communicative; expressing spatial organisations, conditions of privacy and mechanisms of adaptability. This topic of adaptive envelopes and defining thresholds in relation to social complexities has been explored in an architectural design project, which aims to practically address social and environmental issues. This exploration yields a set of key findings into an architecture of thresholds and adaptability in response to the sociotechnical conditions of a context where the lines between the formal and informal are blurred.